Reports on hospitals and the patient and a domestic workers' charter - Great Britain. Standing Joint Committee of Industrial Women's Organisations ; Labour Party (Great Britain). Advisory Committee on Public Health (London : Labour Party, 1931)
1931 1931 1930s 22 pages that we have only 119 replies from domestic servants directly, and 52 from employers. But we have been able — from various meetings and conferences which have been held in various parts of the country and have roused considerable interest, and from Press correspondence — to gain information on which we believe that we can, with considerable confidence, put forward a Domestic Workers' Charter which will be a sound basis for future effort. In giving the results of our inquiries, we have counted the number of persons represented by each reply as well as the number of replies. The answers to the question "What do you think the chief reasons for the unpopularity of domestic service?" must be taken as our starting point. "Long hours" is easily first, but is followed closely by "Lack of Freedom" and dislike of the "Status" and "Loneliness" of the domestic servant. A small number (but one which includes twelve domestic servants) say the chief objection is "Inconsiderate Employers,'' a smaller number give ''Low Wages," and fewer still "Living In." The last, however, is scarcely to be separated from "Lack of Freedom," "Status," and "Loneliness," and, perhaps, also "Long Hours." A smaller number refer to "Poor Food," "Bad Accommodation " and conditions generally, and five replies representing a considerable number of people give the non-insurability against unemployment as the chief objection. It is, therefore, clear that long hours and the general conditions arising from the special status of an employment of this kind, with its lack of freedom and close personal relationship with the employer, are the main reasons why domestic service is unpopular. It is to be noted that "Low Wages," given as the main reason by a very few, is the only reason put forward which could equally well apply to some other employment. All other replies pick out some definite quality peculiar to residential domestic service. It is therefore certain that if this work of caring for the house is to be an acceptable form of employment, the points enumerated above, in the order given, must be specially provided against. In the course of our inquiries we have begun to feel strong doubts as to whether, in fact, the demand for domestic workers is not met by the supply. (17) 126/TG/RES/X/1036A/7